Controlling the structures of organic semiconductor–quantum dot nanocomposites through ligand shell chemistry. Issue 34 (7th August 2020) - Toolan, Daniel T. W.; Weir, Michael P.; Kilbride, Rachel C.; Willmott, Jon R.; King, Stephen M.; Xiao, James; Greenham, Neil C.; Friend, Richard H.; Rao, Akshay; Jones, Richard A. L.; Ryan, Anthony J.
Abstract : Structural insights via small angle X-ray and neutron (SAXS and SANS, respectively) into how nanocrystal quantum dots (QD) functionalized with organic ligands self-assemble with a small molecule organic semiconductor. Abstract : Nanocrystal quantum dots (QD) functionalised with active organic ligands hold significant promise as solar energy conversion materials, capable of multiexcitonic processes that could improve the efficiencies of single-junction photovoltaic devices. Small-angle X-ray and neutron scattering (SAXS and SANS) were used to characterize the structure of lead sulphide QDs post ligand-exchange with model acene-carboxylic acid ligands (benzoic acid, hydrocinnamic acid and naphthoic acid). Results demonstrate that hydrocinnamic acid and naphthoic acid ligated QDs form monolayer ligand shells, whilst benzoic acid ligated QDs possess ligand shells thicker than a monolayer. Further, the formation of a range of nanocomposite materials through the self-assembly of such acene-ligated QDs with an organic small-molecule semiconductor [5, 12-bis((triisopropylsilyl)ethynyl)tetracene (TIPS-Tc)] is investigated. These materials are representative of a wider set of functional solar energy materials; here the focus is on structural studies, and their optoelectronic function is not investigated. As TIPS-Tc concentrations are increased, approaching the solubility limit, SANS data show that QD fractal-like features form, with structures possibly consistent with a diffusion limited aggregation mechanism. These, it is likely, act as heterogeneous nucleation agents for TIPS-Tc crystallization, generating agglomerates containing both QDs and TIPS-Tc. Within the TIPS-Tc crystals there seem to be three distinct QD morphologies: (i) at the crystallite centre (fractal-like QD aggregates acting as nucleating agents), (ii) trapped within the growing crystallite (giving rise to QD features ordered as sticky hard spheres), and (iii) a population of aggregate QDs at the periphery of the crystalline interface that were expelled from the growing TIPS-Tc crystal. Exposure of the QD:TIPS-Tc crystals to DMF vapour, a solvent known to be able to strip ligands from QDs, alters the spacing between PbS–hydrocinnamic acid and PbS–naphthoic acid ligated QD aggregate features. In contrast, for PbS–benzoic acid ligated QDs, DMF vapour exposure promotes the formation of ordered QD colloidal crystal type phases. This work thus demonstrates how different QD ligand chemistries control the interactions between QDs and an organic small molecule, leading to widely differing self-assembly processes. It highlights the unique capabilities of multiscale X-ray and neutron scattering in characterising such composite materials.